Le choix du mode d’occupation sur le marché du logement à Montréal : influence de l’origine ethnique - Laporte, Alain (L'Actualité économique, 1978)
The housing conditions in Montreal are mainly characterized by the two following features: firstly, the high percentage of tenants, secondly, the excessively high proportion of French Canadians in that type of tenure. In spite of this important disequilibrium, there are few systematic analysis of the economic, demographic or cultural factors explaining such a phenomenon. The following paper is aimed at filling this gap. The first part deals with theoretical considerations; the second part contains the specification of the model, the method of estimation and the statistical data used for the estimation; the third part analyses the results and brings up the main conclusions.